PENGARUH KECERDASAN EMOSIONAL, ORGANIZATIONAL CITIZENSHIP BEHAVIOR, KETERLIBATAN KERJA TERHADAP KINERJA PERAWAT RSUD MAJENANG - Alfato Yusnar Kharismasyah; Ericka Esthining Tias Nami Tata; Toufan Aldian syah (Derivatif : Jurnal Manajemen, 2021)
The purpose of this research was to determine the effect of emotional intelligence variables, organizational citizenship behavior, and job involvement on nurse performance. This type of research is quantitative research. Sampling in this study using purposive sampling with a sample size of 115 people. This study took the subjects at the Majenang Regional General Hospital. The data analysis technique used is multiple linear regression analysis. The results of data analysis show that the emotional intelligence variable partially has a significant effect on nurse performance, organizational citizenship behavior partially has a significant effect on nurse performance, job involvement partially has no significant effect on nurse performance and emotional intelligence, organizational citizenship behavior and work involvement simultaneously have an effect significant towards the performance of nurses. Based on the results of data analysis, it shows that the variable organizational citizenship behavior has the most influence on the performance of nurses in the Majenang Regional General Hospital.This research can help make a positive contribution to the Majenang Regional General Hospital, or companies that need to be able to find out how the influence of emotional intelligence, organizational citizenship behavior, and work involvement on nurse performance and provide recommendations for company leaders to be able to determine policies based on conclusions and suggestions of this research.Keywords:Emotional Intelligence, Organizational Citizenship Behavior and Job Involvement on Nurse Performance